2017
DOI: 10.17584/rcch.2017v11i1.6144
|View full text |Cite
|
Sign up to set email alerts
|

Atributos físicos do solo em cultivo de cebola sob sistemas de plantio direto e preparo convencional

Abstract: Este trabalho avaliou os atributos físicos do solo cultivado com cebola em sistemas plantio direto de hortaliças (SPDH) e preparo convencional (SPC) do solo, comparados à área de floresta secundária. Os tratamentos constituíram-se da utilização de plantas de cobertura, solteiras e consorciadas em SPDH agroecológico de cebola por seis anos, em blocos ao acaso com cinco repetições: vegetação espontânea, 100% aveia; 100% centeio; 100% nabo forrageiro; consórcio de nabo forrageiro (14%) + centeio (86%); consórcio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 9 publications
6
15
2
2
Order By: Relevance
“…2). The stratification observed in the MWD coincides with previous studies (Loss, et al, 2017), in which important changes of the MWD were observed, with the depth in soils with different soil use systems and management. This situation can be related to differences of higher organic matter and biological activity, and a higher number of roots in some soil layers, which favor a better size of the stable aggregates.…”
Section: Resultssupporting
confidence: 89%
“…2). The stratification observed in the MWD coincides with previous studies (Loss, et al, 2017), in which important changes of the MWD were observed, with the depth in soils with different soil use systems and management. This situation can be related to differences of higher organic matter and biological activity, and a higher number of roots in some soil layers, which favor a better size of the stable aggregates.…”
Section: Resultssupporting
confidence: 89%
“…It occurs because of the management of the area using the conventional tillage system, with an intense traffic of agricultural machinery (Gennaro et al, 2015). Loss et al (2017) worked with the conventional tillage and notillage systems and observed high Sd values in the CT area, which was attributed to the process of intense soil disturbance.…”
mentioning
confidence: 99%
“…The increase in Bd in NT soils decreased the soil porosity, as reported in previous studies (Silveira et al, 1999;Silva et al, 2008). In contrast, an increase in soil porosity in the surface layer was observed by Loss et al (2017) in vegetables grown under NT compared to conventional tillage, and this result was attributed to the higher number of roots and consequently higher occurrence of voids in the soil matrix. In turn, Costa et al (2003) found no differences in total porosity, macroporosity and microporosity in a Brazilian Latosol managed in the long-term under NT and conventional tillage.…”
Section: Effects On Soil Structurementioning
confidence: 82%